South African state-led pro-Palestinian activism and the reluctance of the academe to show solidarity - Maistry, S. M.; Le Grange, L. (South African Journal of Higher Education, 2025)
South Africa’s higher education landscape remains fragmented and uneven, shaped by a long history of colonialism and apartheid. In this context, this article interrogates the inertia and silence of many South African universities in response to the escalating humanitarian crisis in Palestine, particularly the destruction of educational institutions and loss of academic lives. While the South African government has adopted an unapologetically pro-Palestinian stance—pursuing legal action through international courts—this principled political position has not filtered meaningfully into higher education institutions or the wider public discourse. The article explores the reasons behind the sector’s divergent responses, which range from muteness to active solidarity, and questions the thresholds of tolerance that seem to govern academic inaction. It argues that universities have an ethical and political obligation to engage in development activism as a form of academic activism.